Microstructure, wear and corrosion properties of NiB-TiC composite materials produced by powder metallurgy method - Akkaş Mehmet; Islak Serkan (Science of Sintering, 2019)
In this study, NiB-TiC composite materials were produced using powder metallurgy. In the Ni-TiC-B powder mixture, TiC was fixed at a rate of 5 %, 5, 10 and 15 % boron was added and mechanical alloying was carried out. The prepared powder mixtures were cold pressed under pressure of 400 MPa and sintered in an argon atmosphere at 800°C for 2 hours. Microstructure, phase formation, hardness, wear and corrosion properties of the samples were investigated in detail. Scanning electron microscopy (SEM) was used for microstructure analysis and X-ray diffractogram (XRD) was used for phase formation detection. The hardness measurements of the samples were measured by a microhardness measuring device. Densities of the samples were determined by Archimedes' principle. The corrosion tests were performed potentiodynamic polarization curves of the composite materials in 3.5 % NaCl solution. Wear tests were carried out the composite materials under a load of 10 N. Results showed that by increasing the amount of B, the wear and corrosion resistance increased.